KEPUASAN ANGGOTA TERHADAP PERAN GAPOKTAN DALAM MEMASARKAN BOKAR - Sasmi, Meli; Wardani, Gustia Kusuma; Susanto, Haris (JAS (Jurnal Agri Sains), 2025)
This study aims to determine member satisfaction with the role of Gapoktan Maju Basamo in Titian Modang Kopah Village, Kuantan Tengah District, Kuantan Singingi Regency. Data analysis used IPA and CSI analysis. The results of this study indicate that in quadrant one there are twelve attributes according to important members but their performance is not good. In quadrant two there are eighteen attributes according to members that are important and their performance is good. In quadrant three there are six attributes that according to members are not important and their performance is not good. In quadrant four there are fourteen attributes that according to members are not important but their performance is good. Overall member satisfaction with the role of Gapoktan Maju Basamo is categorized as very satisfied.